Characteristics associated with residential aged care, respite and transitional aged care placement for older people following an injury-related hospitalisation in Australia: IJPDS (2017) Issue 1, Vol 1:127, Proceedings of the IPDLN Conference (August 2016) - Mitchell, Rebecca; Harvey, Lara; Draper, Brian; Brodaty, Henry; Close, Jacqui (International Journal of Population Data Science, 2017)
Objective: This study examines characteristics associated with permanent residential aged care (RAC), respite RAC and transitional care (TC) placement for older individuals following an injury-related hospitalisation. Method: A retrospective analysis of individuals aged ≥65 years who had an injury-related hospitalisation and who had a linked record in RAC, TC or activities of daily living (ADL) data between 1 July 2008 and 30 June 2013 in New South Wales, Australia. Comorbidities were identified using diagnosis classifications and a 1-year lookback period. All hospital episodes of care related to the injury were linked to form a period of care. Both new and existing admissions to RAC were examined. Multinominal logistic regression was used to examine the factors associated with new admissions to permanent RAC, respite RAC and TC compared to return to the community. Results: Of 191,301 injury-related hospitalisations, 41,085 (21.5%) individuals either returned or were new admissions to permanent (87.2%) or respite (12.8%) RAC and 3,218 (1.7%) individuals were admitted to TC. There were 3,864, 4,314 and 2,630 new admissions to permanent RAC, respite RAC and TC, respectively. Of the injury hospitalisations, 70,796 (37.0%) individuals had an ADL assessment. Compared to individuals who returned to the community, individuals newly admitted to permanent RAC were four times as likely to have dementia (OR: 4.36; 95%CI 4.15-4.57), those admitted to respite RAC were twice as likely to have dementia (OR: 2.37; 95%CI 2.21-2.54) and people admitted to TC people were less likely to have dementia (OR: 0.60; 95%CI 0.53-0.68). Individuals with shoulder and upper arm injuries were twice as likely (OR: 2.31; 95%CI 1.98-2.68) and individuals with knee and lower leg injuries were one and a half times as likely (OR: 1.87; 95%CI 1.60-2.18) to be admitted to TC. Overall, individuals who were admitted to permanent or respite RAC had a higher likelihood of experiencing limitations associated with their physical, cognitive or social abilities, with individuals admitted to TC having a higher likelihood of having limitations maintaining personal hygiene and mobility compared to individuals returning to the community. Conclusion: An understanding of the profile of which older individuals are using RAC (permanent or respite) or TC services can usefully inform current and future aged care service use.